2014
DOI: 10.1177/0363546514549004
|View full text |Cite
|
Sign up to set email alerts
|

Knotted Versus Knotless Suture Bridge Repair of the Achilles Tendon Insertion

Abstract: This study demonstrated that the knotless suture bridge repair had a significantly lower load to failure than the knotted suture bridge. Surgeons should be aware of these biomechanical differences, as they influence the postoperative rehabilitation protocol and may lead to higher surgical complication rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 35 publications
4
31
0
Order By: Relevance
“…Additionally, the knotless SutureBridge system (Arthrex Inc) was used in the clinical studies mentioned above. 9,15,17 However, the failure load of the system was 197 N, which was significantly lower than that of the knotted suture bridge, which was 317 N. 7 Because forces in the Achilles tendon are 190 N and 369 N while the patient is walking in a CAM walker with and without a 1-inch heel lift, respectively, 1 the bridging suture alone may not be sufficient to enable accelerated rehabilitation after reattachment of total avulsion of the Achilles tendon.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, the knotless SutureBridge system (Arthrex Inc) was used in the clinical studies mentioned above. 9,15,17 However, the failure load of the system was 197 N, which was significantly lower than that of the knotted suture bridge, which was 317 N. 7 Because forces in the Achilles tendon are 190 N and 369 N while the patient is walking in a CAM walker with and without a 1-inch heel lift, respectively, 1 the bridging suture alone may not be sufficient to enable accelerated rehabilitation after reattachment of total avulsion of the Achilles tendon.…”
Section: Discussionmentioning
confidence: 98%
“…9,15,17 However, biomechanical studies on completely detached Achilles tendons have shown that the suture bridge technique may not have biomechanical advantages over the single-row suture technique. 4,7,14 We describe bridging suture fixation augmented with double Krackow suture for avulsion of the ossified Achilles tendon at its insertion site to restore the stable Achilles tendon insertion.…”
Section: Technique Tipmentioning
confidence: 99%
“…Each specimen was obtained by transecting the Achilles tendon approximately 12 cm proximal to its insertion onto the calcaneus followed by disarticulation of the calcaneus. 7 All specimens were inspected for any preexisting pathology and for gross abnormality. Additional soft tissue was resected until the specimen consisted of only the Achilles tendon and the calcaneus.…”
Section: Methodsmentioning
confidence: 99%
“…This allowed for conditioning elongation and accounts for the toe region on the stress-strain curve. 7 , 10 After the Achilles repair construct was preloaded, the repair length was measured using manual calipers. The measurement was taken from the suture at the most proximal point to the most distal extent of the repair.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation